Studies concerning platinum-catalyzed 1,6-enyne cycloisomerizations: a unified synthetic approach to the Gelsemium alkaloids - Newcomb, Eric Thomas, author; Kennan, Alan, advisor; Ferreira, Eric, committee member; Prieto, Amy, committee member; McNaughton, Brian, committee member; Akkina, Ramesh, committee member (Colorado State University. Libraries, 2015)
The development and application of transition metal-catalyzed enyne cyclization reactions is an ever growing and active area of research in modern organic synthesis. One prolific class of catalysts studied in this broad arena is that of pi-acidic metal complexes. Through further understanding of the fundamental processes of these alkynophilic metal catalysts, we are able to test new transformations in more complex settings. Presented herein are our contributions to the understanding and further implementation of Pt-catalyzed alkyne activation chemistries. In particular, we have developed a chirality transfer protocol to synthesize highly enantioenriched O-tethered cyclopropane-containing compounds. The substrate scope for this process is broad, and the overall transformation is highly stereospecific. Additionally, we further refined a purported mechanistic pathway and extended this chemistry in a number of additional systems. Furthermore, we explored the use of this cycloisomerization chemistry in our synthetic approach to the Gelsemium alkaloids. Specifically, the development of a Pt-catalyzed tandem cycloisomerization/[3,3]-sigmatropic rearrangement allowed us to build a motif shared among a large number of the alkaloids. Following successful implementation of this reaction, we then studied the use of additional late-stage cyclizations to synthesize gelesenicine. Our final two steps, a highly efficient hypervalent iodine-mediated cyclization followed by an iminyl radical cyclization, provided the natural product. Additionally, the synthesis was highly efficient--14 steps--without the use of protecting groups.
Keywords: catalysis; gelsemium; total synthesis; cycloisomerization; alkaloid; platinum